Arbitrage Pricing Theory Model Application on Tobacco and Cigarette Industry in Indonesia - Sakina Ichsani; Neneng Susanti; Agatha Rinta Suhardi (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
The purpose of this study was to applicant the Arbitrage Pricing Theory model in the tobacco and cigarette industry listed on the IDX. The APT model in this study uses macroeconomic variables consisting of exports, inflation, exchange rates, GDP and economic growth. Object of this research is companies listed on the Indonesia Stock Exchange in the period 2012-2017 using monthly periods, which is Gudang Garam Tbk., Handjaya Mandala Sampoerna Tbk., and Bentoel International Investama Tbk. This study uses quantitative methods and analysis will be used with regression analysis methods and data processed using Eviews 10. The results of the study show that there are simultaneous effects between the variables of exports (X1), inflation (X2), exchange rates (X3), GDP (X4), and economic growth (X5) on stock returns (Y). There is a significant positive effect between economic growth on stock returns, while there is a significant negative effect between inflation on stock returns and GDP on stock returns. While exports do not affect the stock returns of the tobacco and cigarette industry as well as the exchange rate does not affect stock returns. Suggestions for investors are if investors are going to invest in the tobacco and cigarette industry, then investors should pay attention to the macroeconomic conditions that affect stocks, while for companies can minimize the risks that might occur through agreements between the destination countries for cigarette sales.